ANALISIS PENGARUH BUDAYA ORGANISASI TERHADAP MOTIVASI KERJA PADA PEGAWAI DINAS KESEHATAN KABUPATEN PEGUNUNGAN BINTANG PROVINSI PAPUA - Akbar, Taufiq (JI@P, 2017)
Organizational culture is a common perception held by members of theorganization into a system of shared meaning that visits of factors ofinnovation and risk taking, attention to detail, results orientation, teamorientation, aggressiveness. While the work motivation is the provision of thedriving force that creates the excitement of a persons work, so that they wouldwork together, to work effectively and integrated with all its resources toachieve the satisfaction that visits of factors physiological needs, safety, social,respect and self-actualization.The method used is the kind of explanatory research-analytic approach studyof 107 employee as samples served in Dinas Kesehatan KabupatenPegunungan Bintang Provinsi Papua and analytical test data analysis pathdiagram / confirmatory factor analysis of Structural Equation Model (SEM).The results showed organizational culture positive and significant effect onwork motivation (CR =10,552 & p = 0.000), factor aggressiveness have astrong effect on organization culture and factor physiological need , social,respect and self-actualization have a strong effect on work motivation.Keywords: Organizational Culture, Work Motivation, and Structural EquationModel(SEM).